A new four-node shell element based on linked interpolation and the desirable displacement field concept - Teerapon Kowsuwan; Worsak Kanok-Nukulchai; Wijeyewickrema, Anil C.; Kishi, Toshiharu; Mahanakorn University of Technology (Bangkok : Asian Institute of Technology, 1998)
A newly developed four-node bilinear shell element based on linked interpolation and Desirable Displacement Field (DDF) concept is formulated for the analysis of general shell. The proposed element is the combination of membrane element and plate element with six degrees of freedom at its vertices. For membrane element, using rigid comer rotations as vertex freedoms, the arbitrary quadrilateral element is presented with the approach of a generalized conforming finite element (Long and Xin, 1989) which is adopted by Long and Xu (1994). The plate element is formulated on Reissner-mindlin theory and transverse displacement is linked to the rotation degree of freedom to ensure high-order interpolation capacity. Condensing it at element level eliminates the internal degrees of freedom, two internal rotational degrees of freedom and two internal shear forces. This efficient plate element, based on Reissner-Mindlin thick plate theory, uses sampling point obtained from Desirable Displacement Field (DDF) concept in assumed strain field of shear. The performance of the proposed element is evaluated by testing the series of benchmark problems in the finite element literature. The numerical results from selected test problems show that except a distorted mesh, the reasonably good accuracy is achieved.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Shells (Engineering)